STRATEGI MENINGKATKAN KEPUASAN MASYARAKAT TERHADAP PENGELOLAAN DANA DESA DIDESA BABULU SELATAN KECAMATAN KOBALIMA KABUPATEN MALAKA - Paula Ruben De Jesus; Petrus E. de Rozari,; Novi Theresia Kiak (Universitas Udayana, 2024)
Village Fund is a fund sourced from the State Budget (APBN) allocated for villages, which is transferred through the Regional Budget (APBD) of the District/City and is used to finance the administration of government, development implementation, community development, and empowerment. This research employs a field research method (survey) conducted in Babulu Selatan Village, Kobalima District, Malaka Regency. The research aims to understand a phenomenon in a natural social context, emphasizing deep communication interactions between the researcher and the phenomenon under investigation. The research results indicate that the Village Fund Management mechanism in Babulu Selatan Village is in line with the technical guidelines for Village Fund management. However, the results of Village Fund management have not been able to maximize community satisfaction because the fund allocation is primarily focused on physical infrastructure development and improvement. Strategies implemented to enhance community satisfaction in villag management through the Village Fund include the following: optimizing aid funds to improve the economy and harness the potential of human resources, enhancing cooperation between the central government and village government, as outlined in a development policy. Keywords: Strategy, Community Satisfaction, Village Fund Management